Safety and efficacy of DOACs vs acenocoumarol in patients undergoing catheter ablation of atrial fibrillation. Issue 10 (31st May 2017) - Vlachos, Konstantinos; Efremidis, Michael; Bazoukis, George; Letsas, Konstantinos P.; Saplaouras, Athanasios; Georgopoulos, Stamatis; Karamichalakis, Nikolaos; Rokiza, Aikaterini; Sakellaropoulou, Antigoni; Kolokathis, Angelos Michail; Efremidis, Theodoros; Asvestas, Dimitrios; et al.
Abstract : Background: Thromboembolic complications can be life‐threatening during atrial fibrillation (AF) catheter ablation. The aim of our study was to evaluate the safety and efficacy of continuous treatment using direct oral anticoagulants (DOACs) as an alternative to uninterrupted acenocoumarol for periprocedural anticoagulation. Hypothesis: Continuous treatment with DOACs has similar safety and efficacy compared to acenocoumarol. Methods: We enrolled 474 patients (mean age, 58 years; 68.4% male) undergoing AF catheter ablation between June 2013 and December 2016. All patients were equally assigned to take acenocoumarol (group 1, 136 patients) or DOACs (group 2, 338 patients) for ≥2 months before the procedure. We compared thromboembolic and bleeding complications between the 2 groups. Results: Our analysis showed no significant difference in major and minor complications between the 2 patient groups. Specifically, 3 of 136 patients (2.2%) using uninterrupted acenocoumarol had a major complication (1 patient [0.7%] had transient ischemic attack resolved 8 hours later, 1 [0.7%] had pericardial tamponade, and 1 [0.7%] had a subcapsular renal hematoma) and 2 patients (1.4%) had minor complications (1 [0.7%] pseudoaneurysm and 1 [0.7%] groin hematoma). In group 2, 1 of 338 patients (0.3%) had a major complication (transient ischemic attack). In the same group, 7 patients (2.1%) had a minor complication (1 patient [0.3%] presented with pseudoaneurysm, 4 [1.2%] with pericardial effusion <1 cm, 1 [0.3%] femoral arteriovenous fistula between the femoral artery and femoral vein, and 1 [0.7%] groin hematoma). Conclusions: DOACs and acenocoumarol have similar safety and effectiveness regarding thromboembolic complications prevention without increasing bleeding complications.